PERANCANGAN APLIKASI AUTOMATIC RESERVATION PADA UNIT PELAYANAN JASA BERBASIS MULTI CLIENT DENGAN SERVER STORAGE (Studi Kasus Unit Pelayanan Jasa Konveksi Toko Gorden Jogjakarta) - ., Andrianto; Fatkhiyah, Erfanti; ., Suraya (Jurnal Jarkom, 2015)
ABSTRACTCurtains vintage is one of the service providers tailor shop as well as sellers of goods curtains, Along with the order to make them quite overwhelmed in terms of bookkeeping. During this time they do the bookkeeping manually, only occasionally copied into the data-processing applications such as Microsoft Excel, which still must be input manually. Under these conditions, it will be created a booking system automatically and computerized, with the system expected to reduce the negligence of the officers, or the ambiguity of data. The system to be used is the customer data collection system, the cost calculation system, the date calculation system, as well as the entire financial report obtained from the service unit. The system uses the Delphi programming platform based on client server, so that each part will be getting its own computer to be able to access the menus on the UPJ. With the system described above, is expected to help employees to recapitalize the transaction and providing the speed and efficiency performance, while providing good service to customersÂ Keywords: Automated Booking System, Desktop Systems, Delphi, Application Services Unit